Green open space analysis in West Binjai, North Sumatra. Issue 1 (November 2021) - Zaitunah, A; Samsuri,; Rojula,; Susilowati, A.; Elfiati, D.; Syahputra, O. K. H.; Arinah, H.; Rangkuti, A.B.; Rambey, R.; Harahap, M. M.; Ulfa, M.; Iswanto, A. H.; et al.
Abstract: West Binjai is a sub-district located in Binjai City, North Sumatra. Green Open Space is also part of the Binjai city's planning scheme which has many benefits for the community and the environment. This research used Normalized Difference Vegetation Index (NDVI) analysis and NDVI value classification results in the distribution of vegetation density. Analysis of changes in vegetation density was carried out between 2015 and 2020 in West Binjai. The largest change in the area of vegetation density classes in the West Binjai between 2015 and 2020 was the increase in the area of the high dense class to 19.13%. The sub-district has green open spaces in the form of sub-district parks, public cemeteries, road green lane, river bank and private green open spaces. These green open spaces were in the low dense, medium, dense and high dense classes. There is a need for rearrangement of green open spaces, especially those within low dense class. Replanting trees are also essential to increase the quality of the green area. Improving the quality of green space will lead to the enhancement of quality of environment.